Comparing structural changes in the rabbit’s uveal tract after the use of a radiowave surgery unit versus a cutting tool (Ukrainian Journal of Ophthalmology, 2025)
Background: Organ-saving treatment strategies for uveal melanoma are still the most common therapeutic approach. Since there is insufficient experience of the use of radiowave surgery technologies, further research is required regarding (a) the effect of a radiowave surgery unit on histology of the tumor and healthy ocular tissues and (b) the changes in post-operative wound healing after implementation of various intervention techniques.Purpose: To assess the response of the sclera and uveal tract to the use of a radiowave surgery unit versus a cutting tool in animals.Materials and Methods: The studies were performed on rabbits taken from the vivarium of the Filatov Institute. A total of 12 Chinchilla adult male rabbits (age, 4–6 months; 12 eyes) were used in the study. Six rabbits of the experimental group (Group 1) underwent monolateral excision of ocular structures (the iris, ciliary body and choroid) with a 4.0-MHz radiowave surgery unit (Surgitron, Ellman International) set on monopolar mode.Results: Histomorphological studies of the ocular tissues (sclera, iris, ciliary body and choroid) in experimental rabbits demonstrated that after surgery with the use of a radiowave surgery unit, necrotic and degenerative changes were observed in the ocular tissues adjacent to the wound canal which had been preserved intraoperative, and these changes expanded to the retina. The changes in the tissues after the use of conventional cutting tools were less apparent.Conclusion: After surgery with the use of a radiowave surgery unit, necrotic and degenerative changes developed in the ocular tissues (ciliary body, scleral and sunconjunctival tissue fragments) adjacent to the wound canal which had been preserved intraoperative. The above changes were maintained, tending to become more severe over 30 days.
Keywords: uvea; radiowave surgery; experimental model; histomorphological changes